2017
DOI: 10.11607/prd.2972
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Effect of Autologous Platelet-Rich Fibrin in the Treatment of Intrabony Defects in Localized Aggressive Periodontitis Patients: A Randomized Controlled Split-Mouth Clinical Trial

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 0 publications
1
30
0
2
Order By: Relevance
“…A PRISMA flow diagram that depicts this selection process is displayed in Figure 1 Table 1. All the 18 studies were RCTs, of which 9 [13,[21][22][23][24][25][26][27][28] were split-mouth design and 9 [29][30][31][32][33][34][35][36][37] were parallel arm design. All the subjects were systematically healthy adults who suffered periodontitis with intrabony defects, except for one study [37] in which participants had periodontal-endodontic lesions with intrabony defects.…”
Section: Study Selection a Total Of 391 Related Articles (78 Inmentioning
confidence: 99%
“…A PRISMA flow diagram that depicts this selection process is displayed in Figure 1 Table 1. All the 18 studies were RCTs, of which 9 [13,[21][22][23][24][25][26][27][28] were split-mouth design and 9 [29][30][31][32][33][34][35][36][37] were parallel arm design. All the subjects were systematically healthy adults who suffered periodontitis with intrabony defects, except for one study [37] in which participants had periodontal-endodontic lesions with intrabony defects.…”
Section: Study Selection a Total Of 391 Related Articles (78 Inmentioning
confidence: 99%
“…Out of 98, 73 articles were further excluded reason being inappropriate control group, use of BGs and other materials etc. Finally a total number of 25 articles[19222324252627282930313233343536373839404142434445] were included for both quantitative and qualitative synthesis and further meta-analysis [Figure 1].…”
Section: Resultsmentioning
confidence: 99%
“…Articles available in electronic form before their publication in printed form were also considered eligible for inclusion in this meta-analysis. One randomized control trial (RCT)[19] was also considered for inclusion which is already accepted for publication in International Journal of Periodontics and Restorative Dentistry (IJPRD), also can be referred at Clinical Trials Registry India No. REF/12/006069.…”
Section: Methodsmentioning
confidence: 99%
“…Third, PRF is easy to prepare and manipulate, and it is inexpensive. [25] Patients receiving dental implants after this sinus floor augmentation surgery with PRF technology showed a 100% survival rate with a mean follow-up of 33 months. [26] In addition, Dohan et al [21] showed that PRF also plays a crucial role in suppressing inflammatory reactions, thus acting as a node of immune regulation; these effects were attributed to the release of anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%